The correlations between illness perception and self-care in chronic kidney disease patients undergoing hemodialysis - Nur Widayati; Marsya Nurrahmawati; Akhmad Zainur Ridla; Muhamad Toha (Nursing and Health Sciences Journal (NHSJ), 2025)
Self-care has become a concern among chronic kidney disease (CKD) patients undergoing hemodialysis due to limitations in performing self-care and daily activities. An individual's perception of their illness plays a crucial role in coping with and adapting to the condition. This study aimed to analyze the correlation between illness perception and self-care in CKD patients undergoing hemodialysis. This research was a correlational descriptive design with a cross-sectional approach. Ninety-seven respondents participated in this study. Data were collected using the Brief Illness Perception Questionnaire (B-IPQ) and the Self-care of CKD index and analyzed using Spearman's rank test with a significance level of 0.05. The mean of illness perception was 37.16 ±10.29, and the median of self–care was 68 (45-91). There was a significant negative correlation between illness perception and self-care in CKD patients undergoing hemodialysis (p=0.003 and r=-0.299). Illness perception is related to self-care in CKD patients undergoing hemodialysis—the more positive the illness perception, the lower the patient's dependence on self-care. Therefore, improving illness perception is essential to optimize self-care in CKD patients undergoing hemodialysis.